Generalized separation of variable for nonlinear equation utt=a(t)uxx+b(t)u2x+c(t)uutt=a(t)uxx+b(t)ux2+c(t)u - Barannyk, Anatoliy; Barannyk, Tatiana; Yuryk, Ivan (My University, 2015)
We propose a generalized procedure of separation of variables for nonlinear equations and construct broad classes of exact solutions of these equations that cannot be obtained by the classical Lie method and the method of conditional symmetries.
Keywords: кафедра вищої математики імені проф. Можара В. І.; nonlinear hyperbolic equations; generalized separation of variables; нелінійні гіперболічні рівняння; узагальнене відокремлення змінних; нелинейные гиперболические уравнения; обобщенное разделение переменных